An assessment of lifestyle and weight status during COVID-19 pandemic among Raipur city’s population (International Journal of Food and Nutritional Sciences, 2023)
The aim of this study was an assessment of lifestyle and weight status during COVID-19 pandemic among Raipur city’s population. A cross-sectional descriptive survey method was conducted among 1000 sample sized for collection data. Chosen sample area was Raipur city and tools for collecting data were - Schedule, GPS TEST APP digital, weighing machine, Inch tape. Used GPS TEST App for tracking sample, with help of GPS Test collect data for survey, filled up the schedule. Results show that, all 1000 samples responded to the schedule. A Sedentary lifestyle results shows 504, (50.4(%) and physically active lifestyle – 496 (49.6%), Sleeping Habits - Less than 7 hours 85 (8.5%), 7 hours - 456 (45.6%), 7-9 hours- 143, (14.3%), 9 hours- 316 (31.6%). Weight Status of Subjects Based on Lifestyle Sedentary – Underweight - 205 (40.7) (61.2) Normal 259 (51.4) (43.5) Overweight -24 (4.8) (58.5) Obese 24 (4.8) (58.5) Class I - 12 (2.4) (75.0) Obesity Class III – 4 (0.8) (33.3). Physically Active lifestyle - Underweight 130 (26.2) (38.8) Normal weight - 337 (67.9) (56.5) overweight - 17 (3.4) (41.5) Obese - 4 (0.8) I (25.0) class- 8(1.6) (66.7). The conclusion of results suggested that the COVID-19 pandemic triggered a variety of lifestyle changes and physically active changes. Key words: lifestyle, weight status, covid-19.